2004
DOI: 10.1021/jp049380r
|View full text |Cite
|
Sign up to set email alerts
|

New Nanoparticle Formation under UV Impact on Acetaldehyde Vapor in Nitrogen and Air Flow

Abstract: This paper deals with the study of the kinetics of photolysis and photonucleation of acetaldehyde (AA) vapor in air and in nitrogen along with physical and chemical characteristics of the formed aerosol particles. Free radicals accompanying photonucleation were identified using the electron spin resonance spin-trapping technique. Numerical modeling of the photonucleation kinetics of AA, based on experimental results, was carried out. Rate of generation of primary products, leading to the nanoparticles, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Because the calculation showed that the formation of a cluster with the participation of the carbonyl group of one BA molecule and the aromatic ring of another BA molecule is advantageous from the viewpoint of energy, it was interesting to check how the association of other aldehyde molecules (including those having no aromatic groups) could be predicted by the above-described calculation procedure. A detailed chemical analysis of the gaseous and aerosol products of the photolysis of CH 3 CHO carried out previously exhibited no dependence of glyoxal yield on water-vapor content. To test the adequacy of the theoretical approach proposed here, we calculated the energy of a similar clustering process in acetaldehyde.…”
Section: Calculationsmentioning
confidence: 92%
“…Because the calculation showed that the formation of a cluster with the participation of the carbonyl group of one BA molecule and the aromatic ring of another BA molecule is advantageous from the viewpoint of energy, it was interesting to check how the association of other aldehyde molecules (including those having no aromatic groups) could be predicted by the above-described calculation procedure. A detailed chemical analysis of the gaseous and aerosol products of the photolysis of CH 3 CHO carried out previously exhibited no dependence of glyoxal yield on water-vapor content. To test the adequacy of the theoretical approach proposed here, we calculated the energy of a similar clustering process in acetaldehyde.…”
Section: Calculationsmentioning
confidence: 92%
“…This process leads directly to the formation of phenoxyl radical PhCO • and further to aerosol products. If the transformation really takes place in such a way, it becomes clear why the aerosol formation efficiency for BA photolysis in air is not so much different from that in inert gas as it was observed for acetaldehyde and formaldehyde photolysis 14,24 The most active radicals produced during photolysis in air and in nitrogen in the latter two systems sharply differ from each other in reactivity.…”
Section: Analysis Of the Chemical Composition Of The Gas And Aerosol ...mentioning
confidence: 94%
“…The aerosol formation kinetics was studied with the setup similar to that described elsewhere. , Figure shows the schematic of the setup. It consists of the flow reactor (5) (22 mm inner diameter, ca.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations